Devonian tentaculitoidea of the malvinokaffric realm of Brazil, paraná basin - Comniskey, Jeanninny Carla; Ghilardi, Renato Pirani [UNESP] (Coquina Press, 2018)
The Tentaculitoidea is represented by extinct invertebrates characterized by small, conic, carbonate shells of animals that inhabiting exclusively marine environments. The tentaculitoids occur from the Ordovician to Devonian, with diversity peaking in the Middle Devonian. The Tentaculitoidea has three orders: Tentaculitida (benthic habit), Homoctenida, and Dacryoconarida (planktonic habit). In Brazil, the oldest tentaculitoids occur in strata of the early Silurian, with the genus Tentaculites. Specimens of the Dacryoconarida and Homoctenida orders were only found in the Lower Devonian strata. In this study, we conducted taxonomic analyses of specimens in collections from various research institutions, including samples used in the last systematic study with this group, in mid-1991. The present study aims to review the systematic aspects of the tentaculitoids of the Devonian strata, Paraná basin, Brazil. Seven species of tentaculitoids were identified: two species previously described, Tentaculites jaculus and Tentaculites crotalinus and five news species: Tentaculites kozlowskii, Tentaculites paranaensis, Uniconus ciguelii, Homoctenus katzerii, and Styliolina langenii. This is the first known occurrence of the genus Uniconus in Devonian strata from Brazil. The analyzed species of homoctenids and dacryoconarids are larger than those previously described in the specialized literature. This study demonstrated that the tentaculitoids of the Paraná Basin have a stratigraphic distribution from the end of the Pragian to the early Givetian.
Keywords: Apucarana sub-basin; Brazil; Class tentaculitoidea; Devonian; New species; Systematics